Peningkatan Penguasaan Konsep “Kebijakan Fiskal dan Moneter” Melalui Model Pembelajaran Mandiri Aktif Bermedia Audio Visual pada Siswa Kelas XI-1 SMA Negeri 4 Kediri - Elis Irmayanti; Bayu Surindra (Proceedings of The ICECRS, 2019)
This research is a type of classroom action research using a collaborative model with 4 steps in each action. The object of action is the application of an active self-directed audio media learning model is VCD. The action has been done in 2 cycles with the research subject class XI-1 SMA Negeri 4 Kediri. The formulation of the problem includes: 1) How are the steps of the teacher in applying the concept of active self-learning in audio visual media. 2) How are the steps of the teacher in increasing student involvement in teaching and learning activities. 3) Whether the application of the concept of active self-learning with audio visual media can increase students mastery of the concept of “fiscal and monetary policy”. The conclusion is: 1) From the teacher’s point of view, steps have been found to apply the concept of active self-learning with audio visual/VCD media to improve the mastery of the concepts of “fiscal and monetary policy”. 2) From the teacher’s point of view, steps have been found to apply the concept of active self-learning with audio visual/VCD media to increase student involvement in teaching and learning activities. 3) From the student’s point of view, it has been successfully proven that the application of the concept of of active self-learning with audio visual/VCD media to improve the mastery of the concepts of “fiscal and monetary policy”.